Incentivos económicos para promover la movilidad sostenible universitaria - Barrionuevo Mora, María de los Angeles (2023)
Sustainable mobility seeks to satisfy transportation needs, both private and public, minimizing environmental impacts. To achieve this, a model must be promoted that, among others, prioritizes alternative and collective mobility, reduces the use of fossil fuels and single-occupant vehicles, promotes shared mobility and optimizes parking management. Higher education institutions seeking to implement a sustainability model must prioritize this approach, given that the movement of students, staff and visitors to and from campus represents one of the main sources of environmental and social impact they generate. The study focused on the administrative staff at the Quito headquarters of the Pontificia Universidad Católica del Ecuador, the first private university in the country. The possibility of eliminating free parking service was analyzed as a way to promote environmental co-responsibility. The research determined that the arithmetic mean of the value that the participants were willing to pay for parking was $16.11 USD and $32.56 USD for institutional transportation per month. Through two Logit models, variables that influence willingness to pay for hypothetical sustainable mobility scenarios were identified; It was determined that variables such as income level, environmental perceptions, sociodemographic information and the availability of exclusive and safe parking spaces influence the willingness. Based on these results, a proposal for economic incentives for the sustainable management of parking lots can be proposed